Horrid Henry:Stinkbombs! - Simon,Francesca (Great Britain: Orion Children's Books, 2002)
Horrid Henry's Stinkbomb is another hilarious installment in the Horrid Henry series by Francesca Simon, with illustrations by Tony Ross. In this book, Henry is up to his usual naughty tricks across four mischievous short stories. The title story, Horrid Henry's Stinkbomb, follows Henry as he plots revenge on Moody Margaret during a prank war between boys and girls $1 (Band the stinkbomb is his secret weapon. Other stories in the book include: Horrid Henry Reads a Book, where Henry struggles to enjoy reading and comes up with a sneaky way to win a book report contest. Horrid Henry's School Project, where his laziness leads to a very unconventional project. Horrid Henry's Sleepover, where he causes chaos while staying at someone else$1 (Bs house overnight. Each tale is filled with humor, exaggerated behavior, and Henry$1 (Bs wild imagination. The book explores themes like rivalry, cleverness, and the consequences of mischief, making it a favorite among young readers, especially those who enjoy funny and fast-paced stories.s
Horrid Henry$1 (Bs Stinkbomb is part of the best-selling Horrid Henry series by Francesca Simon, illustrated by Tony Ross. Aimed at children aged 6 to 10, the book contains four short stories filled with humor, mischief, and exaggerated childhood behavior. The title story centers around a prank war between boys and girls, showcasing Henry$1 (Bs over-the-top tactics and creative rule-breaking. The other stories offer equally chaotic and funny scenarios, reflecting Henry$1 (Bs unwillingness to follow rules or behave like his well-mannered brother, Perfect Peter. Written in accessible language and supported by energetic illustrations, the book is ideal for emerging and reluctant readers. It uses humor to highlight themes such as rivalry, laziness, clever problem-solving, and the unintended consequences of bad behavior. As with other books in the series, it$1 (Bs both entertaining and relatable for children, particularly those navigating school life and sibling relationships.s
Keywords: Pranks and mischief; School life